Can We Re-Imagine Research So It Is Timely, Relevant and Responsive?; Comment on "Experience of Health Leadership in Partnering with University-Based Researchers in Canada: A Call to 'Re-Imagine' Research" - Cecilia Vindrola-Padros (Kerman University of Medical Sciences, 2021)
Partnerships between academic institutions and healthcare organisations have been proposed as an effective way to integrate academic research findings into changes in health policy and practice. Bowen and colleagues explore these partnerships from a different angle, analysing them in relation to the experiences of health system leaders. The authors made a call to re-imagine research, rethinking how we train applied health researchers, fund health research and evaluation and design studies and collaborations with the health sector. In this paper, I respond to this call by discussing three strategies we can use to make sure our research is timely, relevant and responsive to the needs and context of healthcare organisations: the widespread use of rapid research approaches, the integration of scoping stages in all studies, and the training of applied health researchers to work in the health system and develop collaborative relationships with staff.